Enhancing Engineering Students Attention and Concept Retention: Insights from Synesthetic Learning and Microteaching - Bharath, B. M.; Bavatharani, R.; Sharma, Naresh Kumar; Lakshmi Narasimhan, V. (Journal of Engineering Education Transformations, 2026)
In the present education scenario, there is a growing trend towards continued student interaction and support of the retention of complicated engineering concepts. Conventional education renders classes passive. Numerous students lose concentration and reason less. Multisensory techniques assist the student to connect new concepts to familiar ones. They also demonstrate the fitment of ideas. Compared in this paper are Synesthetic Learning Pedagogy (SLP) and Microteaching (MT). The two supplement sound and brief activities to improve attention and memory. MT involves teachers to provide brief lessons in order to develop understanding and articulated speech. SLP involves the utilization of sight, sound, and movement to make the lessons more interesting. Pilot classroom tests involving a population of about 130 B. Tech students showed considerable improvement of up to 47 percent in concept retention in the long term as compared to the control. Although SLP can be employed to boost retention, its complete effects on creativity and learning require further investigation. This was carried out among engineering students of varying year levels. The findings demonstrate the influence of every approach on the concentration of students and their ability to remember what they have learned. The paper recommends that application of various teaching ways depending on learning objectives, has the propensity of preferring the attentiveness and assimilation of instructional material.